Hepatischer Hydrothorax ohne Aszites - Schöder, H.; Friedrich, M. (Nuklearmedizin - NuclearMedicine, 1991)
A case of hepatic hydrothorax without clinical ascites is reported. The diagnosis was confirmed by intraperitoneal injection of 99mTc-tin colloid: scintigraphic images taken between 5 min and 18 h p.i. demonstrated a oneway transdiaphragmatic flow into the pleural cavity. The therapy consisted of diuretic treatment, pleural drainage and chemical pleurodesis, and resulted in prompt clinical improvement.